Electoral accountability, clarity of responsibility and labor market policy. (December 2020) - Marinova, Dani M.
Abstract: Does the exercise of accountability in elections have palpable policy effects? Building on recent advances in the economic voting literature, we show that electoral accountability leaves an imprint on labor market policy when left-wing governments are in office. When responsibility for the economy is clear and elections offer an opportunity to claim credit for economic expansion, labor protections and benefits become more generous. However, when clarity of responsibility is low and incumbents can expect to veer electoral responsibility, left-wing governments are more likely to retrench labor market policy. These results hold for policies benefiting both labor market insiders and outsiders. Consistent with evidence that the labor market is the purview of the left, electoral accountability does not condition labor market policy under right-wing governments. We discuss the implications of these results in the context of growing party system fragmentation and weaker accountability across advanced industrial democracies.